The model of three-subject relations in the educational process of the university - Шульга, Наталія Вікторівна (Pedagogy of Higher and Secondary Education, 2015)
Shulga N. V. The model of three-subject relations in the educational process of the university. The model of three-subject relations in the educational process is represented in the article. Its components: the teaching subject, the learning subject and the subject that determines the information and communication learning environment (ICLE) have been characterized. The main characteristics of teaching and learning subjects are operating, worldview and reflective components. ICLE structure is defined according to the communication strategy, organization features and forms of elements interaction.